2019
DOI: 10.3399/bjgpopen19x101653
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable effect of individualised sun protection advice on sun protection behaviour: a 10-year follow-up of a randomised controlled study in primary care

Abstract: Background: In the light of increasing skin cancer incidences worldwide, preventive measures to promote sun protection in individuals with risky sun habits have continued relevance and importance.Aim: To report the long-term effect of individualised sun protection advice given in primary health care (PHC), on sun habits and sun protection behaviour.Design & setting: In 2005, 309 PHC patients were enrolled in a randomised controlled study performed in a Swedish PHC setting.Method: At baseline, the study partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Thus, skin cancer is often referred to as highly preventable, as primary preventive measures can be directed at promoting accurate sun protection to individuals, or groups of individuals, with the highest risk due to phenotypic, environmental, and behavioural factors [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In order to be able to do so, there is a need for valid and reliable tools to measure sun exposure habits and sun protection behaviour, both in order to identify individuals with a risky behaviour with regard to skin cancer, as well as to be able to communicate individually tailored sun protection advice [ 18 , 19 , 20 ]. For this purpose, the Sun Exposure and Protection Index (SEPI) has previously been developed and validated in English and in Swedish, as well as in two opposing UVR environments (Australia and Northern Europe) [ 21 ], and since then used as a measure in both epidemiologic and experimental studies [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, skin cancer is often referred to as highly preventable, as primary preventive measures can be directed at promoting accurate sun protection to individuals, or groups of individuals, with the highest risk due to phenotypic, environmental, and behavioural factors [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In order to be able to do so, there is a need for valid and reliable tools to measure sun exposure habits and sun protection behaviour, both in order to identify individuals with a risky behaviour with regard to skin cancer, as well as to be able to communicate individually tailored sun protection advice [ 18 , 19 , 20 ]. For this purpose, the Sun Exposure and Protection Index (SEPI) has previously been developed and validated in English and in Swedish, as well as in two opposing UVR environments (Australia and Northern Europe) [ 21 ], and since then used as a measure in both epidemiologic and experimental studies [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to be able to do so, there is a need for valid and reliable tools to measure sun exposure habits and sun protection behaviour, both in order to identify individuals with a risky behaviour with regard to skin cancer, as well as to be able to communicate individually tailored sun protection advice [ 18 , 19 , 20 ]. For this purpose, the Sun Exposure and Protection Index (SEPI) has previously been developed and validated in English and in Swedish, as well as in two opposing UVR environments (Australia and Northern Europe) [ 21 ], and since then used as a measure in both epidemiologic and experimental studies [ 19 , 22 , 23 ]. It is composed of two parts; part 1 addresses present sun exposure habits, and part 2 the propensity to increase sun protection.…”
Section: Introductionmentioning
confidence: 99%
“…These observations not only point to the limits of cognitive capacity to drive preventive behaviour but also the crucial educational role of dermatologists, together with general practitionners. 20 The present online survey does have some limitations. The findings may be affected by the inherent bias of declarative surveys, including cognitive and memory bias.…”
Section: Items Of Thementioning
confidence: 96%
“…In Australia, where skin cancer is a major public health concern, the SunSmart prevention program succeeded in improving sun protection behaviour over the 30 years from 1987 19 . Several studies have also shown that sun protective behaviours have improved; thanks to guidance from primary care general practitioners, 20 through counselling by dermatologists, 21 and via appearance‐based interventions 22,23 . There is however nothing to suggest that the incidence of sunburn in children or adults has sustainably decreased as a result of these interventions 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas these predisposing factors cannot be altered, behavior in the sun certainly can, being the major target for primary prevention efforts. The challenge in this respect is for relevant healthcare providers to properly communicate measures of prevention and motivate people as to why it is important, and how to override possible obstacles to appropriate sun protection (4,5). An important aspect in this regard is to identify and direct preventative action to those who need it the most, i.e.…”
mentioning
confidence: 99%